Social Influence, Self Awareness, and Social Media in Sustainable Fashion Purchase Intention as Far as the Eye Sees Generation Z: The Role of Perceived Value - Septiana, Nia; Salomo Anthonino Kumenaung, Dean; Faruqi, Faris; Hendryadi, Hendryadi (Lembaga Penelitian Universitas YARSI, 2026)
Objective: This study examines the effects of social influence, self-awareness, and social media on sustainable fashion purchase intention among Generation Z, with perceived value as a mediating variable. Methods: A quantitative causal-associative approach was applied. Data were collected through online questionnaires distributed via Google Forms to Generation Z respondents aged 18–27 who were familiar with sustainable fashion products. A total of 190 valid responses were analyzed using SmartPLS. Findings: The results show that social influence, social media, and perceived value positively and significantly affect sustainable fashion purchase intention among Generation Z, while self-awareness has a positive but insignificant effect. Moreover, self-awareness and social media significantly influence perceived value, whereas social influence does not. Perceived value mediates the effects of self-awareness and social media on purchase intention but does not mediate the effect of social influence. Originality and Contributions: This study enriches empirical research on sustainable fashion consumption among Generation Z in Indonesia and emphasizes the role of perceived value as a partial mediator. Focusing on Sejauh Mata Memandang consumers, the findings offer practical insights for sustainable fashion marketing strategies.